The corruption of the presidents of progressivism and plutocracy - Albornoz, César (2018)
This article analyzes cases of corruption involving presidents of two important periods of Ecuadorian political history: the so-called progressive governments between 1884 and 1895 and the plutocratic governments between 1901 and 1906 and, once liberal radicalism was defeated, between 1912 and 1925, in usufruct of the power for the benefit of bankers, exporters, importers and great landowners and allies to prevent any advance of the ideas of radical liberalism in the country.